DEVELOPMENT OF ETHNOSCIENCE-BASED DIGITAL TEACHING MATERIALS IN AUTHENTIC JEMBER PATROL MUSIC IN SOUND SUB MATERIALS FOR STUDENTS IN JUNIOR HIGH SCHOOL - Rafiatul Hasanah; Winda Dwi Kusumawati (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Culture is the wealth of the Indonesian nation while education is an intermediary for forming the character of the nation's successor. Learning in schools is an interaction that helps students understand learning materials, especially conceptual and factual learning. One of them is in learning Natural Sciences (IPA), in the field of Physics. Noise material is a conceptual material with a discussion of sound waves produced by vibrating objects (sound sources). Based on the needs analysis obtained, the development of appropriate teaching materials to explain the material is a digital book. The purpose of this study is to describe the level of validation of teaching materials and describe student responses to ethnoscience-based digital teaching materials in Authentic Jember Patrol music on sound sub-materials in class VIII SMP/MTs students. The type of research used is the development of a 4-D model. The subject of validity in this study involved material experts and media experts and science teachers, with the results of material validation being 91.03%, media experts 89, 41%, and user experts (teachers) 88, 23% very valid categories. While the student response test in this study was divided into 2, namely, small-scale test and large-scale test with an average percentage result of 80.76% with a valid category, and large-scale trials obtained an average percentage of 87.28% with a category very, without any revisions to the developed teaching material products.